Development of cultivars that expand the area of almond cultivation: commemorating the 120th birthday of Prof. Alexander An. Richter - A. A. Richter (Труды по прикладной ботанике, генетике и селекции)
The name of Alexander An. Richter, a prominent scientist in the field of breeding new cultivars of nut crops and subtropical fruit plants, is widely known worldwide. A winner of the USSR State Prize, Prof. Dr. A. Richter was second in the world to develop a program of almond cultivation and breeding, thus making a significant contribution to the development of horticulture in the south of Russia. Over thirty new cultivars released in the course of many years made it possible to expand adaptation of cultivated almond to various regions of Southern Russia. Prof. A. Richter continued Nikolay Vavilov’s mission to mobilize and utilize plant genetic resources, contributing to the promotion of this nut crop and the broadening of industrial almond cultivation areas. Years of his participation in the USSR Exhibition of Achievements of National Economy (VDNKh) earned him numerous gold medal awards.